Supplementation with high-content docosahexaenoic acid triglyceride in attention-deficit hyperactivity disorder: a randomized double-blind placebo-controlled trial - Rodríguez C; García T; Areces D; Fernández E; García-Noriega M; Domingo JC (Neuropsychiatric Disease and Treatment, 2019)
Celestino Rodríguez,1 Trinidad García,1 Débora Areces,1,2 Estrella Fernández,1 Marcelino García-Noriega,3 Joan Carles Domingo41Department of Psychology, Faculty of Psychology, University of Oviedo, Oviedo, Spain; 2Child Education Program, Faculty Padre Ossó, Oviedo, Spain; 3Service of Pediatrics, Hospital Valle del Nalón, Langreo, Spain; 4Department of Biochemistry and Molecular Biomedicine, Faculty of Biology, University of Barcelona, Barcelona, SpainBackground: Attention-deficit hyperactivity disorder (ADHD) is a complex disorder in terms of etiology, clinical presentation, and treatment outcome. Pharmacological and psychological interventions are recommended as primary treatments in ADHD; however, other nonpharmacological intervention such as a dietary supplementation with omega-3 polyunsaturated fatty acids (ω-3 PUFAs) has emerged as an attractive option.Purpose: The objective of the present study was to assess whether dietary supplementation with highly concentrated ω-3 docosahexaenoic acid (DHA) triglyceride may improve symptoms in ADHD.Method: A 6-month prospective double-blind placebo-controlled randomized clinical trial was designed in 66 patients with ADHD, aged between 6 and 18 years. Participants in the experimental group received a combination of ω-3 fatty acids (DHA 1,000 mg, eicosapentaenoic acid 90 mg, and docosapentaenoic acid 150 mg). Instruments included d2-test, AULA Nesplora, EDAH scales, and abbreviated Conner’s Rating Scale.Results: In the cognitive test, between-group differences were not found, but within-group differences were of a greater magnitude in the DHA group. Between-group differences in favor of the DHA arm were observed in behavioral measures, which were already detected after 3 months of treatment. Results were not changed when adjusted by ADHD medication.Conclusions: This study provides further evidence of the beneficial effect of supplementation with ω-3 DHA in the management of ADHD.Keywords: omega 3, PUFAs, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), attention-deficit hyperactivity disorder (ADHD)